Palliative therapy for osteosarcoma. Issue 2 (February 2011) - Errani, Costantino; Longhi, Alessandra; Rossi, Giuseppe; Rimondi, Eugenio; Biazzo, Alessio; Toscano, Angelo; Alìì, Nikolin; Ruggieri, Pietro; Alberghini, Marco; Picci, Piero; Bacci, Gaetano; Mercuri, Mario
Despite advances in diagnostic imaging, the evolution of neoadjuvant chemotherapy and the refinements in limb-salvage surgery, the progression-free survival rate remains poor for patients with metastatic, recurrent or unresectable osteosaroma. Different therapeutic strategies for these subgroups of patients have been employed to control disease and prolong survival. Treatment options are limited and controversial, including systemic and localized therapies. Surgical resection, whenever feasible, is still the standard treatment in advanced osteosarcoma. The role of chemotherapy is unclear while the use of radiotherapy, embolization and thermal ablation is increasing. New therapeutic experimental approaches and novel target therapies are needed to improve the outcome of these subgroups of patients.